Maximal Respiratory Pressures, their Association with Spirometric Parameters, Swimming Skills and Changes Due to Immersion in Water (Baltic Journal of Sport and Health Sciences, 2013)
Research  background  and  hypothesis.  We  checked  hypothesis  that  swimming  skill  improvement  is  more dependent on inspiratory muscle strength than endurance volume to be ventilated.Research aim was to determine associations between maximal static inspiratory (MIP) and expiratory (MEP) pressures, swimming skills, parameters of forced spirometry. Research methods. Investigation involved 62 female students (age 22.13 ± 1.3 years, height 168.4 ± 6.6 cm, and weight 61.3 ± 7.0 kg) of the Latvian Academy of Sports Education. All of them were non-smokers. Swimming skills in four strokes were evaluated by a swimming coach. MIP and MEP were measured at the mouth level outside the swimming pool and repeated in the swimming pool while the subject was immersed up to the neck level. Forced spirometry was performed according ATS guidelines outside the water. Research  results.  Average  value  for  MIP  outside  the  water  was  109  ±  30  cm  H 2 0  and  for  MEP  it  was 147 ± 33 cm H 2 0. There was positive correlation between peak expiratory flow and MIP, MEP, and the rate of increase of both pressures (p < 0.05). Forced vital capacity was not related to maximal pressures. Faster rate of inspiratory pressure increase was positively related to forced inspiratory volume in one second (p < 0.05). There was a significant decrease of MIP and the rate of increase of inspiratory pressure in the immersion state while no changes of expiratory parameters were observed. Discussion and conclusions. Swimming skill improvement is more dependent on inspiratory muscle strength than volume to be ventilated. Students with higher PEF have higher respiratory pressure parameters. Immersion in water decreases MIP, IMRPD and increases IMMRR. Changes of these parameters due to immersion are not related  to swimming skills.Keywords: maximal inspiratory pressure, maximal expiratory pressure, swimming education, immersion in water.